Analysis of Bankruptcy Prediction with Financial Ratios Altman Z-Score Model: Case Study of Oil and Gas Companies Listed on IDX in 2017-2021 - Denari Dhahana Edtiyarsih (West Science Interdisciplinary Studies, 2023)
Because Indonesia has abundant oil and natural gas, companies that manage oil and natural gas have established themselves there. The advent of these businesses will most likely result in rivalry. So, in this study, we will use the Altman Z-score ratio to assess the probability of bankruptcy in oil and gas companies listed on the IDX. The population targeted is individuals working in the mining sector, which produces oil and gas and is traded on the Indonesian Stock Exchange. A total of seven samples were collected. The data collection technique is a documentation technique that involves gathering secondary data with the requirements received from www.idx.co.id (IDX official website). The data analyst used panel data regression analysis with reviews. The data analyst employed is panel data regression analysis using reviews. The results of the study showed that the ratio used has a significant effect on bankruptcy prediction with the Altman Z-score model. They are evidenced by the value of f count (46.6564) > f table (2.6896) with a significance of 0.000 <0.05.